2017
DOI: 10.1007/s40262-017-0539-z
|View full text |Cite
|
Sign up to set email alerts
|

Gestation-Specific Changes in the Anatomy and Physiology of Healthy Pregnant Women: An Extended Repository of Model Parameters for Physiologically Based Pharmacokinetic Modeling in Pregnancy

Abstract: The presented results facilitate the integration of pregnancy-dependent changes in anatomy and physiology into mechanistic population physiologically based pharmacokinetic models. Such models can ultimately provide a valuable tool to investigate the pharmacokinetics during pregnancy in silico and support informed decision making regarding optimal dosing regimens in this vulnerable special population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
182
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 94 publications
(208 citation statements)
references
References 369 publications
3
182
0
1
Order By: Relevance
“…While body weight and composition substantially change during pregnancy, it is much more complex to scale them in a nonmechanistic model. Furthermore, the body weight of the adult subjects involved in the previous study was reported to be 72.3 kg, which corresponds roughly to the body weight of a typical pregnant woman at 30 weeks’ gestation . Therefore, it was decided to scale the clearance while keeping the central volume constant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While body weight and composition substantially change during pregnancy, it is much more complex to scale them in a nonmechanistic model. Furthermore, the body weight of the adult subjects involved in the previous study was reported to be 72.3 kg, which corresponds roughly to the body weight of a typical pregnant woman at 30 weeks’ gestation . Therefore, it was decided to scale the clearance while keeping the central volume constant.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the volume of distribution of the central compartment was higher in the mother compared to the neonate, and also when normalized to body weight, neonatal volume of distribution was higher compared to that of the mother (0.320 vs 0.405 L/kg). In the neonate, the extracellular water fraction of total body weight is higher compared to the mother . Because ceftazidime distribution is mainly confined to the extracellular water, the higher volume fraction of watery compartments in the fetal/neonatal organism corresponds to a dilution effect, which can explain the higher weight‐normalized volume of distribution.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation in the development of pregnancy PBPK models is the availability of data regarding changes in physiological parameters affecting drug disposition and clinical pharmacokinetic data for model verification. Several groups have cataloged a number of physiological changes across gestation . However, these data often come from a variety of literature sources, which may have been obtained using inaccurate methods .…”
Section: Physiologically Based Pharmacokinetic Models Of Pregnancymentioning
confidence: 99%
“…Several groups have cataloged a number of physiological changes across gestation . However, these data often come from a variety of literature sources, which may have been obtained using inaccurate methods . In some cases, these data are based on studies in nonpregnant women or animals.…”
Section: Physiologically Based Pharmacokinetic Models Of Pregnancymentioning
confidence: 99%
See 1 more Smart Citation